2022
DOI: 10.21037/tp-21-289
|View full text |Cite
|
Sign up to set email alerts
|

Cellular congenital mesoblastic nephroma detected by prenatal MRI: a case report and literature review

Abstract: Congenital mesoblastic nephroma (CMN) is a rare tumor, yet it is the most frequently diagnosed renal neoplasm in the first 3 months of life. CMN reports with prenatal magnetic resonance imaging (MRI) are scarce. Our aims were to describe a case with fetal MR imaging along with other findings, and to review the literature concerned with prenatal MRI detection of CMN. Upon routine ultrasound (US) examination of a 36-week pregnant woman, a fetal abdominal mass was disclosed. Prenatal MRI revealed a large, well-ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 20 publications
1
6
1
Order By: Relevance
“…No CMN patient of our cohort had metastasis, confirming the very low metastatic risk of this tumour 18 . Nevertheless, CMN with distant metastases has been reported in rare cases, mainly in association with the cellular subtype 22–24 . Compared to previous studies, we found a higher risk of distant metastasis for CCSK (13% vs. 4%–7%) 15,17 .…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…No CMN patient of our cohort had metastasis, confirming the very low metastatic risk of this tumour 18 . Nevertheless, CMN with distant metastases has been reported in rare cases, mainly in association with the cellular subtype 22–24 . Compared to previous studies, we found a higher risk of distant metastasis for CCSK (13% vs. 4%–7%) 15,17 .…”
Section: Discussionsupporting
confidence: 76%
“…18 Nevertheless, CMN with distant metastases has been reported in rare cases, mainly in association with the cellular subtype. [22][23][24] Compared to previous studies, we found a higher risk of distant metastasis for CCSK (13% vs. 4%-7%). 15,17 The association of older age, larger TV and more advanced tumour stage in our series of WT was recently also reported in a large SEER cohort of 3463 patients 25 (Supplemental Consistent with previous work, we identified CMN as the most common kidney tumour up to 3 months of age.…”
Section: Incidence Bilaterality and Metastasiscontrasting
confidence: 83%
“…Congenital mesoblastic nephroma as a separate entity was first described by Bolande et al and classified as a benign renal tumor [ 9 , 10 ]. Nevertheless, given limited reports of metastatic behavior, it is currently best classified as a mesenchymal tumor with low malignant potential [ 2 , 5 , 11 14 ]. Morbidity and mortality are predominantly caused by associated polyhydramnios and other related paraneoplastic syndromes at presentation, whereas the tumor rarely metastasizes, mainly to the lungs, brain, liver, or bone [ 11 , 15 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Based on previous case reports and small retrospective studies, congenital mesoblastic nephroma is typically described as homogeneous and isointense to normal renal parenchyma [ 4 , 7 , 12 , 14 , 33 ]. The cellular type seems to be more heterogeneous, making differentiation from malignant tumors more difficult [ 3 , 6 , 8 , 21 , 28 , 33 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…CMN can be prenatally diagnosed by ultrasound and MRI. Several case/series reports of the prenatal diagnosis of CMN have been scatteringly published in the literature, and they are increasing in number [ 2 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. However, to the best of our knowledge, the prenatal features and outcomes of pregnancies with fetal CMN have never been systematically reviewed and analyzed, whereas neonatal and pediatric series have been published several times.…”
Section: Introductionmentioning
confidence: 99%